The Role Of The Human Development Index on Regional Economic Growth in Java and Sumatra, 2014–2023 - Olos Wasahua; Sumaryoto; Karno (PT Maju Malaqbi Makkarana, 2026)
Economic growth is the main indicator in measuring the progress and welfare of a region. In the perspective of modern development, economic growth is not only determined by physical factors such as investment and capital, but also by the quality of human resources reflected through the Human Development Index (HDI). This study aims to analyze the effect of HDI on economic growth in the provinces of Java and Sumatra during the period 2014–2023. The data used are panel data from 16 provinces (6 in Java and 10 in Sumatra) with the Fixed Effect Model (FEM) approach selected based on the results of the Chow and Hausman test. The results show that HDI has a positive and significant effect on economic growth, with a coefficient value of β = 1.161 and a t-statistic value of 9.206 > t-table 1.658 and a probability value of 0.0000 < 0.05. The elasticity value E > 1 indicates that an increase in HDI is elastic to economic growth, meaning that each increase in HDI will increase economic growth proportionally greater. These results reinforce the human capital theory, which states that investment in education, health, and a decent standard of living is key to sustainable economic growth. The study also found that the HDI's influence on economic growth was stronger in Java than in Sumatra due to differences in education quality, infrastructure, and urbanization. The policy implications of this study are the need for local governments to strengthen investment in vocational education, workforce training, and improving basic health services to reduce disparities in human development between regions.